Effect of business risk and profitability on the capital structure of consumer goods companies listed on the Indonesia stock exchange before and during COVID-19 pandemic - DEDE NOFIALDI; AIMATUL YUMNA (Universitas Negeri Padang, 2021)
The COVID-19 pandemic is a condition of the spread of SAR-CoV-2 (coronavirus) that attacks the human respiratory system. Indonesia's COVID-19 pandemic began when the first case was confirmed on March 2, 2020. The COVID-19 pandemic is often analogous to a